Strengthening the father-child bond - Prinsloo, Christina (Reineth) (Groupwork, 2012)
Incarceration of men causes many children to lose their fathers to imprisonment temporarily. Parenting programs often ignore or exclude incarcerated fathers. The involvement in criminal activities and the resulting incarceration does not exempt the fathers from their roles and responsibilities. The human element of rehabilitation and family relationships cannot be ignored. For many children of incarcerated parents, the best permanency plan is one in which the parent continues to play a significant role in the child’s life. The preservation of families, even in a prison setting, is a priority. The aim of this article is to describe the nature of a fatherhood-skills project with groupwork as the main method of intervention in a prison setting and the influence in alleviating the impact of incarceration on family members. The specific aim of the project was to strengthen family ties between incarcerated fathers and their children. Groupwork with the aim to improve fatherhood skills was done after a thorough situation analysis of inmates’ needs. Fathers had to show motivation to be better fathers to be involved in the groupwork. The result of the project was an extended day visit for fathers and children and an ongoing effort in the specific prison to improve the skills of the fathers.